Theoretical framework for the determinants and management of food safety problem: A case study of the waste cooking oil issue in China - Chen, Chuangbin; Chitose, Atsushi; Kusadokoro, Motoi; Bao, Ligao; Nie, Haisong (Frontiers in Sustainable Food Systems, 2022)
The public health issue of waste cooking oil in China has been a well-known food safety problem since 2010. To prevent this food safety from getting worse, the Chinese government has immediately promulgated regulations. Food safety researchers also recommended several associated solutions; however, this food safety persists more than ten years later. Accompanied it continuing to plague Chinese residents; therefore, a systematic reassessment of the determinants and management of the waste cooking oil issue is increasingly critical. Existing studies do not include research into the models and determining factors for this issue. To explore the dominant influences of this food safety and provide recommendations to the relevant legislators, this paper develops a theoretical framework for the determinants and management of food safety problems. Unlike previous research based on first-hand data and the principles of grounded theory analysis research method, this novel research is the first attempt to employ second-hand data from 152 court judgments collected from the official database of China Judgements Online. The results demonstrate that legal loopholes, food hygiene inspectors, and consumer self-protection consciousness are the three crucial determinants of this food safety. Besides, offender crime patterns and case characteristics also play an essential role. Based on the findings, we propose three management guidelines for Chinese legislation: redefining the waste cooking oil issue, raising the hot-pot restaurant sanitation permission threshold, and improving overall food safety awareness and education in communities. Our research findings could provide a theoretical basis for China’s waste cooking oil issue and other food safety issues worldwide.